Effects of Organizational Control, Trust, Relationship Commitment, and Partnerships on Relationship Performance in the Business Waste Industry - Wen-Chih, Yeh; Ming-Hsun, Tseng; Chun-Chang, Lee (International Journal of Asian Social Science, 2018)
This study aimed to explore the effects of organizational control, relationship commitment, trust, and partnerships on industrial relationship performance. The participants in the survey were legitimate civil private companies that deal with waste disposal and treatment (both domestic and foreign companies) and are located in the six special municipalities of Taiwan. A questionnaire survey was conducted. A total of 1,000 questionnaires were distributed, and 550 questionnaires were returned. An effective sample of 539 questionnaires was collected, for an effective recovery rate of 98%. Analyses were performed using structural equation modeling (SEM). The results indicated significant positive effects of relationship control on formal control, relationship control on relationship commitment, relational trust on institutional trust, institutional trust on partnerships, and partnerships on relationship performance. These results can provide business waste organizations with a reference for the coordination of organizational control and decisions related to relationship performance management.